Elective Cesarean Section during Preterm Prevents Pulmonary Hypoplasia Development in Potter Sequence - Yuya Kinoshita; Rieko Sakamoto; Yusuke Hattori; Keishiro Furuie; Shohei Kuraoka; Yuko Hidaka; Hiroshi Tamura; Hiroshi Mitsubuchi; Kimitoshi Nakamura (Hindawi Limited, 2023)
Potter syndrome, first reported in 1946 by Edith Potter, refers to fatal cases of bilateral renal aplasia with pulmonary hypoplasia, peculiar facial features, and limb deformities. Presently, patients with oligohydramnios showing similar pathological manifestations due to oligohydramnios caused by conditions other than bilateral renal aplasia have been reported, and are known as the Potter sequence. There are limited studies and unclear guidelines on the safest delivery time and detailed postpartum management for patients with the Potter sequence. We experienced a case of Potter sequence, in which the patient was born by elective cesarean section at gestational age (GA) of 34 weeks. Fetal ultrasound at GA of 26 weeks 4 days showed oligohydramnios, multilocular cystic lesions in the left kidney, and an absent right kidney. Prenatal fetal MRI at GA of 33 weeks and 3 days showed pulmonary hypoplasia, and the ratio of fetal lung volume (FLV) to fetal body weight (FBW) was 0.0135 ml/g. We suspected that the fetal lung could not grow because of persistent oligohydramnios, which leads to a further decline in the ratio of FLV to FBW during pregnancy. We performed a cesarean section at GA of 34 weeks to prevent the exacerbation of the imbalance between lung volume and physique. We struggled to keep her condition stabilized with strict management of her respiratory condition, dialysis, and nutrition. She was discharged from the hospital at 169 days of age. Elective caesarean section in the term of premature birth prevented the progression of pulmonary hypoplasia and made it possible to save her life. Potter sequence is still relatively unknown, and it is necessary for more studies to be conducted in the future.